Differentiated effects of the multimodal antidepressant vortioxetine on sleep architecture: Part 2, pharmacological interactions in rodents suggest a role of serotonin-3 receptor antagonism - Leiser, Steven C (J Psychopharmacol, 2015)
Antidepressants often disrupt sleep. Vortioxetine, a multimodal antidepressant acting through serotonin (5-HT) transporter (SERT) inhibition, 5-HT(3), 5-HT(7) and 5-HT(1D) receptor antagonism, 5-HT(1B) receptor partial agonism, and 5-HT(1A) receptor agonism, had fewer incidences of sleep-related adverse events reported in depressed patients. In the accompanying paper a polysomnographic electroencephalography (sleep-EEG) study of vortioxetine and paroxetine in healthy subjects indicated that at low/intermediate levels of SERT occupancy, vortioxetine affected rapid eye movement (REM) sleep differently than paroxetine. Here we investigated clinically meaningful doses (80–90% SERT occupancy) of vortioxetine and paroxetine on sleep-EEG in rats to further elucidate the serotoninergic receptor mechanisms mediating this difference. Cortical EEG, electromyography (EMG), and locomotion were recorded telemetrically for 10 days, following an acute dose, from rats receiving vortioxetine-infused chow or paroxetine-infused water and respective controls. Sleep stages were manually scored into active wake, quiet wake, and non-REM or REM sleep. Acute paroxetine or vortioxetine delayed REM onset latency (ROL) and decreased REM episodes. After repeated administration, vortioxetine yielded normal sleep-wake rhythms while paroxetine continued to suppress REM. Paroxetine, unlike vortioxetine, increased transitions from non-REM to wake, suggesting fragmented sleep. Next, we investigated the role of 5-HT(3) receptors in eliciting these differences. The 5-HT(3) receptor antagonist ondansetron significantly reduced paroxetine’s acute effects on ROL, while the 5-HT(3) receptor agonist SR57227A significantly increased vortioxetine’s acute effect on ROL. Overall, our data are consistent with the clinical findings that vortioxetine impacts REM sleep differently than paroxetine, and suggests a role for 5-HT(3) receptor antagonism in mitigating these differences.